Rancang Bangun Sistem Monitoring Kinerja Main Engine Kapal Berbasis IOT - Aditya Putra Mahendra; Sri Mulyanto Herlambang; Prima Yudha Yudianto (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
Main engine is the main driving engine. This research develops a ship's main engine temperature monitoring system using the Blynk application. Thermocouple sensors measure engine temperature and IR Sensor measure RPM, the data is processed by ESP32, and sent to the Blynk cloud server, this research aims to determine the design of a prototype intelligent monitoring system to detect the temperature of a ship's main engine using a Thermocouple sensor, NodeMCU ESP32 which operates at 3.3V power is used as the processing core data. The system design in this research integrates Internet of Things (IoT) technology. Test factors for thermocouple temperature measuring devices and RPM sensors (IR Sensors). The test procedure uses a dynamo as a simulation of the main engine, tested for 5-10 minutes under normal conditions and 5 minutes when the dynamo feels warm to hot.